“Yeah, suicide is a white thing”: Problematizing the Reclamation of the Ghosts of Suicide in David Bradley’s The Chaneysville Incident and Toni Morrison’s Beloved - Wilde, E (2011)
Both The Chaneysville Incident and Beloved investigate the slippery subject of suicide, as they expose and explore what happened to formerly enslaved men and women who chose death rather than a return to slavery. Both Morrison and Bradley choose to use ghosts to allow those who have committed suicide to speak of their experiences, thus negating the imposition of social, political or religious opinions on the suicide act from the wider living community. However restrictions placed on these ghosts by these authors leads not only to exclusions and limitations for understanding the dead based on gender, but also causes such confusion that the reader is unsure what is being concluded about suicide in these novels. Ultimately, both Bradley and Morrison use complicated language and formatting strategies to make suicide a subject which cannot be clearly described or explained, advocating the view that suicide is an unreadable blankness, and dismissing critical readings of their works by Ryan and Marouan, who see suicide as being a mode of political discourse.